Preparation of graphene/poly(vinyl alcohol) composite hydrogel films with enhanced electrical and mechanical properties. Issue 3 (17th October 2019) - Alam, Ashraful; Moussa, Mahmoud
Abstract: Electrically conductive and robust composite hydrogel films are the increasing demand for compact and portable energy storage systems and biosensor. We herein present a simple route for electrically conductive and strong graphene/poly(vinyl alcohol) (PVA) composite hydrogel films by a casting method using processable graphene sheets. Both pure PVA and graphene/PVA composite hydrogel films were characterized by various techniques including scanning electron microscopy (SEM), X‐ray diffraction (XRD), electrical, and mechanical measurements. High‐quality, processable graphene sheets effectively enhanced the composite's electrical conductivity; a percolation threshold was achieved at 4.6 vol% of graphene mass loading. At 10 wt% nanomaterials loading, Young's modulus, and tensile strength improved by 369% and 930%, respectively, compared with neat PVA hydrogel films. The significant reinforcement found in composite films containing water attributed to strong interface between water, high‐quality graphene sheets, and PVA polymer chains. As supercapacitor electrodes, composite hydrogel film delivered a gravimetric capacitance of 9.5 F/g. This work provides a new approach for fabricating electrically conductive hydrogel films using nonconducting polymer for supercapacitor.